Hepatoprotective Activity of Methanolic Extract of Mallotus philippensis (Lam.) muell.-arg in Rats - Geetha, K.M.; Ramakrishna, S.; Sridhar, C.; Murugan, V. (Asian Journal of Chemistry, 2010)
The main objective of the study is to investigate the hepatoprotective properties of the methanolic extract of the Mallotus philippensis (Euphorbiaceae) leaves, against ethanol induced liver damage in albino rats. The methanolic extract of Mallotus phillipensis was evaluated for potential hepatoprotective activity in albino rats by ethanol induced hepatotoxicity after pretreatment with two different doses (100 mg/kg and 200 mg/kg b.w, p.o) of methanolic extract of the Mallotus philippensis. Silymarin (25 mg/kg) served as standard hepatoprotective agent. Ethanol produced significant changes in physical (increased liver weight and volume), biochemical (increase in serum alanine transaminase, aspartate transaminase, alkaline phosphatase, direct bilirubin, total bilirubin, cholesterol, triglycerides and decrease in total protein level), antioxidant (catalase, superoxide dismutase and lipid peroxidation), histological (damage to hepatocytes) and functional (thiopentone-induced sleeping time) liver parameters. Pretreatment with methanolic extract of the Mallotus philippensis leaves significantly prevented the physical, biochemical, antioxidant, histological and functional changes induced by ethanol in the liver. The present study indicates that methanolic extract of the Mallotus philippensis leaves possessed hepatoprotective activity in the doses used.